How food retailing changed in Turkey: spread of self-service technologies. Issue 2 (5th February 2018) - Kazancoglu, Ipek; Kursunluoglu Yarimoglu, Emel
Abstract : Purpose: The purpose of this paper is to predict customers' intentions to use self-checkouts based on the technology acceptance model (TAM). Design/methodology/approach: The questionnaire consisted of constructs taken from the existing literature such as perceived ease of use (PEU), perceived usefulness (PU), behavioral intentions, technology anxiety (TA), perceived risk (PR), need for interaction (NI), and situational factors (SF). Before preparing the questionnaire, the focus group studies were organized to gain deeper insights regarding customers' views about self-checkouts. Based on the results of the focus groups, some items in the constructs were adapted, and the questionnaire was generated. The field study was conducted via face-to-face survey with 500 customers chosen by stratified random sampling. Confirmatory factor analysis and structural equation modeling were used to validate the relationships hypothesized in the conceptual model among constructs. Findings: Out of the 16 hypotheses, 10 were found to be significant. The hypotheses related to the effects of PR, PEU, PU, intentions, while the effects of NI on PU and intentions; the effects of SF on intentions were not accepted in the study. According to the findings, PEU, PU, and TA affected intentions whereas PR, NI, and SF did not. Research limitations/implications: There were some limitations related to demographics, attitudes, SF, and actual usage of self-checkouts. Practical implications: To avoid queues, retailers should install a sufficient number of user-friendly and simple interfaced self-checkouts with well-trained employees to encourage usage and reduce the perceived risk and anxiety. Originality/value: The main contribution of this study was that the effects of different constructs were measured on Turkish customers' intentions to use self-checkouts, which could be used in formulating marketing strategies as well as considering future research directions. The paper also provided additional insights into the effects of SF, TA, NI, and PR, all of which were added to the TAM in this study.